2022
DOI: 10.3389/fgene.2022.806607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Copy Number Variants in Gene Co-Expression Patterns for Luminal B Breast Tumors

Abstract: Gene co-expression networks have become a usual approach to integrate the vast amounts of information coming from gene expression studies in cancer cohorts. The reprogramming of the gene regulatory control and the molecular pathways depending on such control are central to the characterization of the disease, aiming to unveil the consequences for cancer prognosis and therapeutics. There is, however, a multitude of factors which have been associated with anomalous control of gene expression in cancer. In the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
8
1
Order By: Relevance
“…The assessment of the contribution of different regulatory elements such as enhancers, transcription factor binding sites, CTCF binding sites, and Hi-C contacts, to the local gene co-expression in normal tissues done by (21) indicated that no feature can uniquely explain the co-expression patterns observed, but they all contribute in a complementary fashion. We have shown, for Luminal A and B breast cancer subtypes, that intra-chromosomal communities are not bound by CTCF binding sites and that copy number alterations do not influence co-expressed network communities with a similar differential expression trend (27) nor do they affect intra-cytoband co-expression patterns (63). Our group has also analyzed epigenetic mechanisms in the context of cancer gene co-expression, in particular the role of miRNA regulation, showing that specific miRNA families alter coexpression in genes related to the epithelial-mesenchymal transition (64, 65), they also promote subtype-specific pathways in breast cancer (66), and are associated with progression stage in clear cell renal carcinoma (67).…”
Section: Discussionmentioning
confidence: 97%
“…The assessment of the contribution of different regulatory elements such as enhancers, transcription factor binding sites, CTCF binding sites, and Hi-C contacts, to the local gene co-expression in normal tissues done by (21) indicated that no feature can uniquely explain the co-expression patterns observed, but they all contribute in a complementary fashion. We have shown, for Luminal A and B breast cancer subtypes, that intra-chromosomal communities are not bound by CTCF binding sites and that copy number alterations do not influence co-expressed network communities with a similar differential expression trend (27) nor do they affect intra-cytoband co-expression patterns (63). Our group has also analyzed epigenetic mechanisms in the context of cancer gene co-expression, in particular the role of miRNA regulation, showing that specific miRNA families alter coexpression in genes related to the epithelial-mesenchymal transition (64, 65), they also promote subtype-specific pathways in breast cancer (66), and are associated with progression stage in clear cell renal carcinoma (67).…”
Section: Discussionmentioning
confidence: 97%
“…However, the mechanism for which this phenomenon emerges in cancer, but not in control, networks remains elusive. We have investigated the role of other biomolecular processes such as those in transcription factor binding sites, CTCF binding sites (30), or copy number alterations (75). It is worth noticing that none of them has shown to be significantly related to the loss of inter-chromosomal interactions.…”
Section: Mir-217 Is Differentially Expressed In All Sequentially Cont...mentioning
confidence: 99%
“…This result shows that there are remarkable differences between the cancer regulation programs at the transcription and the translation levels, indicating the importance of multiomics analysis to understand the general biomolecular expression regulatory program. Efforts in this line may include (but are not limited to) the analysis of micro-RNA-gene co-expression analysis [ 47 , 48 ], copy number alteration’s role in the co-expression landscape [ 31 , 49 ], epigenetic regulation [ 50 ], among others.…”
Section: Discussionmentioning
confidence: 99%